Upaya Pemerintah Dalam Membangun Rekonsiliasi dan Pencegahan Konflik Sejak Dini Di Kalimantan Barat - Syamsuwir, Syamsuwir; Fakhrurrazi, Fakhrurrazi (PASAI, 2014)
Talking about Government Efforts in Building Reconciliation and Conflict Prevention in West Kalimantan since Dini, the vision of "Safe" is the right step to make it happen and is in line with the efforts concerned. The word "safe" in that vision implies that although the background is very heterogeneous community life they can still live together in a harmonious atmosphere, synergy and mutual understanding. Therefore, it is necessary to state that interdependence is inevitable in the life of society, nation and state. "Safe" is a dynamic concept because it recognizes that the interdependence of life and the ever-changing conditions, both constellation, perimbangannya, and the values that underlie and influence. Society "Safe" is a society that is able to realize a democratic political culture and tolerance, people who are able to put those individuals in a position parallel to and equal before the law and people who can always put the public interest above personal or group interests. To strengthen security, must be upheld development more equitable and just. In addition, law enforcement and the implementation of the principles of good governance is the key to realizing secure West Kalimantan.